Species differentiation by DNA-modified carbon electrodes using an ac impedimetric approach. - Davis, Frank; Nabok, Alexei; Higson, Seamus P. J. (Elsevier Science B.V., Amsterdam., 2005)
A simple and novel electrochemical biosensor based approach is described for differentiating between differing species of fish on the basis of DNA hybridisation events. Screen-printed carbon electrodes modified with a variety of polymers were used to immobilise commercially available DNA in a single- stranded form. AC impedimetric measurements were firstly carried out on these systems and then upon exposure to single-stranded DNA solutions. When the electrode and solution DNA were complementary, a large drop in impedance was measured; this did not occur for non-matching DNA exposures. DNA hybridisation sensors for closely related species of fish were in the first instance developed as a demonstration for this approach. Species of fish such as herrings and salmon could be differentiated by this method. This sensor format offers great promise for many DNA hybridisation applications and lends itself to mass fabrication due to the simplicity and inexpensiveness of the materials and methods used. The hybridisation results were confirmed by use of ellipsometry to measure the characteristics of similar films deposited on silicon substrates.
Keywords: Carbon electrode; DNA hybridisation; DNA detection; AC impedance; Ellipsometry